Influenza vaccine uptake in the elderly population: Individual and general practitioner's determinants in Central Italy, Lazio region, 2016–2017 season. Issue 36 (23rd August 2019) - Fabiani, Massimo; Volpe, Enrico; Faraone, Maurizio; Bella, Antonino; Rizzo, Caterina; Marchetti, Stefano; Pezzotti, Patrizio; Chini, Francesco
Abstract: Background: Elderly people are a priority target group for influenza vaccination and their decision to be vaccinated might partly depend on advice received from general practitioners (GP). This study aims to investigate the association between influenza vaccine uptake in the elderly residents in the Lazio region of Italy and the demographic and professional characteristics of their GPs, taking simultaneously into account the elderly's individual characteristics. Methods: We used data retrieved from different administrative sources to retrospectively analyse the cohort of 1, 255, 657 elderly residents aged ≥65 years who were alive and registered in the regional healthcare service at the beginning of the 2016–2017 influenza vaccination campaign (1 Oct. 2016–31 Jan. 2017). We assessed influenza vaccine uptake at the end of the vaccination campaign and evaluated its association with both individual and GP-related characteristics through a multilevel Poisson regression models accounting for clustering at physician level. Results: Overall, vaccination coverage at the end of vaccination campaign was 50.6%. Elderly residents who were male, older, vaccinated in the previous seasons, living in smaller provinces, and spending more money for specialist medical care showed a significantly increased probability to be vaccinated. Vaccine uptake was also significantly higher in the elderly residents assisted by GPs who got master's degree more recently, assisted a relatively high proportion of elderly patients, received influenza vaccination, had a computer assistant, and were associated with other physicians. Conclusions: Our results indicate that influenza vaccination coverage in the elderly residents of the Lazio region is still unsatisfactorily low. We identified several determinants of influenza vaccine uptake, related to both individual and GP characteristics. Understanding how GP characteristics affected influenza vaccine uptake in the elderly population might provide insight on GPs' attitudes and concerns regarding influenza vaccination, allowing the implementation of targeted evidence-based interventions to sensitise GPs and increase vaccination coverage.